USM TO CONTINUE MOULDING SOCIAL WORKERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 21 March 2016 – Universiti Sains Malaysia (USM) is the first university in the country to offer a course in social work since 1975.